The COVID-19 pandemic increased the incidence of newly diagnosed cancers: evidence from a large cohort study in Southern Italy - Valentina Trimarco; Raffaele Izzo; Daniela Pacella; Maria V. Manzi; Fahimeh Varzideh; Maria Lembo; Paola Gallo; Roberto Piccinocchi; Carmine Morisco; Francesco Rozza; Gaetano Piccinocchi; Michelangelo Mercogliano; et al. (BMC Medicine)
Abstract Background Recent studies based on hospital and outpatient clinic databases have reported a decline in cancer diagnoses during the COVID-19 pandemic, an observation that has been mainly attributed to halted screenings. Methods We investigated the impact of COVID-19 on cancer incidence in the Campania Region (Italy) among adults followed by their primary care physicians over a 6-year period (2017–2022). Using a single-cohort design, we employed interrupted time series (ITS) analysis to compare cancer incidence rates during the 3 years preceding the pandemic (2017–2019) with those during the three pandemic years (2020–2022). Results We analyzed data from 212,656 individuals and found that the incidence of new cancer diagnoses rose from 14.3 to 23.1 per 1000 person-years when comparing the pre-pandemic to the COVID-19 period. ITS analysis revealed a stable trend in cancer diagnoses before the pandemic, followed by a marked increase of ~8 new cases per month beginning in January 2020, with a peak observed in August 2021. Notably, diagnoses of brain and skin cancers increased by 300% in 2022 compared to 2017. Conclusions Taken together, these findings highlight a concerning increase in cancer diagnoses in the Campania Region during the COVID-19 pandemic, contrasting with earlier reports that pointed to a decline in cases, mostly attributed to interrupted screening services. Several indirect factors might contribute to this trend, including heightened psychosocial stress and shifts in lifestyle behaviors, as well as profound disruptions in access to and continuity of healthcare delivery.